2008
DOI: 10.1002/jnr.21869
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic receptor stimulation protects nigral dopaminergic neurons in rotenone‐induced Parkinson's disease models

Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease and is characterized by dopaminergic (DA) neuronal cell loss in the substantia nigra. Although the entire pathogenesis of PD is still unclear, both environmental and genetic factors contribute to neurodegeneration. Epidemiologic studies show that prevalence of PD is lower in smokers than in nonsmokers. Nicotine, a releaser of dopamine from DA neurons, is one of the candidates of antiparkinson agents in tobacco. To assess the protectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(74 citation statements)
references
References 55 publications
3
71
0
Order By: Relevance
“…Previous studies have suggested that a4b2 and a6b2 subtypes of nicotinic acetylcholine receptors (nAChRs) contribute to the neuroprotective effects of the stimulant, although other nicotinic subunits also likely contribute (Ryan et al, 2001;Khwaja et al, 2007;Takeuchi et al, 2009;Quik et al, 2011). For example, a4b2 antagonist administration inhibits the protection afforded by nicotine in rotenonetreated mice (Takeuchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that a4b2 and a6b2 subtypes of nicotinic acetylcholine receptors (nAChRs) contribute to the neuroprotective effects of the stimulant, although other nicotinic subunits also likely contribute (Ryan et al, 2001;Khwaja et al, 2007;Takeuchi et al, 2009;Quik et al, 2011). For example, a4b2 antagonist administration inhibits the protection afforded by nicotine in rotenonetreated mice (Takeuchi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a4b2 antagonist administration inhibits the protection afforded by nicotine in rotenonetreated mice (Takeuchi et al, 2009). Furthermore, the protective effect of chronic nicotine against 6-hydroxy-DA was lost in a4-knockout mice (Ryan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to lesion other animal species such as mice or monkeys have not been successful at all [72,92]. However, recent studies by two groups have demonstrated that oral administration of rotenone to mice causes nigral degeneration, a decrease of striatal dopamine levels, and motor dysfunction [85,93,94]. They also demonstrated α-synuclein aggregation in different areas of the brain [95].…”
Section: Rotenonementioning
confidence: 99%
“…Found to activate the AMPK/SIRT1/autophagy pathway in cellular models of PD [172], reseveratrol and idebenone have been shown to increase longevity and delay agerelated deterioration of motor functions in HtrA2 knockout PD mice [180].…”
Section: Resveratrol and Idebenonementioning
confidence: 99%